Hopped‐frequency waveform design for range sidelobe suppression in spectral congestion. Issue 1 (1st January 2018) - Zhao, Dehua; Wei, Yinsheng; Liu, Yongtan
Abstract : By properly transmitting pulses through the clear frequency bands, the hopped‐frequency (HopF) waveform can achieve a large synthetic bandwidth while avoiding the complexity of wideband hardware as well as the mutual interference to/from adjacent RF users. To optimally design the HopF waveform with low range sidelobes under given spectral constraints, we propose a two‐step‐based approach in this paper. In the first step, a deterministic approach is presented to produce a rough approximation of the optimum solution to address the non‐convexity of the waveform design. In the second step, gradient method is applied to locally refine the solution obtained in the first step. The proposed design method is efficient as the main computation in the first step lies in solving a convex optimisation which can be achieved in polynomial time and the iterative operations in the second step can be implemented using non‐uniform fast Fourier transform. Experimental evidence suggests that the proposed method can produce near optimal solution in remarkably little time.